Environmental Aspects and Public Concern for the Environment as Part of Sport Diplomacy at the 2018 Asian Games - Nur Aslamiah Supli; Retno S usilowati; Inda Mustika Permata (Program Pascasarjana Universitas Sriwijaya, 2020)
The environmental aspects and the community's environmental concern are an inseparable part of the Sports Diplomacy at the 2018 Asian Games. This study is aimed at examining the environmental aspects and environmental concerns of the community. Researchers used explorative and descriptive methods. The sampling technique in this study is purposive sampling. Data were gathered using online questionnaires in a google form for likert scale 1-5. The results showed that all the public facilities were considered to be sufficient for visitors to the Jakabaring Sport city during the 2018 Asian Games. Based on the asked opinions with likert scales 1-5 it was found that the respondents’ opinions on the environmental aspects of the games’ facilities were quite good to very good, which included the availability of clean water, garbage boxes, availability of public toilets and smoke-free zones. Less than 10 percent of respondents are concerned about the adequacy of clean water and other public facilities.